Heart attack encroaching fourth decade: autopsy study of western Maharashtra - Thokal, Mansi; Narayankar, Shilpa; Patil, Saurabh (International Journal of Research in Medical Sciences, 2024)
Background: Indians are known to have the highest coronary artery disease (CAD) rates, and the conventional risk factors fail to explain this increased risk. At present, India has the highest burden of acute coronary syndrome and ST-elevation myocardial infarction (MI). Methods: An autopsy study of 6 years: January 2015 to December 2020 which included heart specimens affected by MI from medicolegal autopsies received in histopathology section. The received heart specimens were fixed in 10% formalin and processed as per routine histotechniques with H&E stain and slides prepared were studied under light microscopy. Results: Maximum number of myocardial infarction cases 21 (23.5%) were seen in the age group of 41-50. Commonest histopathological pattern noted was Healed myocardial infarction 38 (42.6%), followed by acute myocardial infarction (AMI) 29 (32.5%) then acute with healed myocardial infarction (AHMI) 22 (24.7%). Conclusions: Atherosclerosis being the most common cause of MI but frequency of non-atherosclerotic myocardial infarction is rising in 4th decade which is a matter of concern. The study of human atherosclerotic lesion is an extremely difficult task in a living subject and an autopsy study is the best possible way to work on it.